2011
DOI: 10.1177/1045389x11418860
|View full text |Cite
|
Sign up to set email alerts
|

Compact and Lightweight Hydraulic Actuation System for High Performance Millimeter Scale Robotic Applications: Modeling and Experiments

Abstract: In this work, the design modeling and testing of a compact and lightweight hydraulic actuation system is presented. Compared to similar compact actuators found in the literature, our system considerably increases the work density while maintaining an equivalent force-to-volume ratio. An analytical model that is able to accurately predict the quasi-static behavior of the actuator has been developed and experimentally validated. Existing models in the literature are able to predict only one performance parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 11 publications
0
14
1
Order By: Relevance
“…The reported maximum (blocked) forces covered a wide range with the larger diameter muscles generated the higher forces. Three previous studies used similarly small diameter braids as used in the present work of less than 6 mm [16,20,24]. The maximum contraction (free) strains from these small diameter braids were of a similar magnitude (~20%) and the maximum blocked forces were either similar or lower than those reported in the present study.…”
Section: Effect Of the Unloaded Muscle Length On Isometric Force Genecontrasting
confidence: 51%
See 1 more Smart Citation
“…The reported maximum (blocked) forces covered a wide range with the larger diameter muscles generated the higher forces. Three previous studies used similarly small diameter braids as used in the present work of less than 6 mm [16,20,24]. The maximum contraction (free) strains from these small diameter braids were of a similar magnitude (~20%) and the maximum blocked forces were either similar or lower than those reported in the present study.…”
Section: Effect Of the Unloaded Muscle Length On Isometric Force Genecontrasting
confidence: 51%
“…Moreover, it has been shown that it was possible to design relatively 'large' pneumatic McKibben muscles to actuate human limb-size robots [22], or even very powerful ones thanks to the use of a particular strong external braided sleeve [23]. In an alternative way, it is also possible to develop microscale HAMs like the ones proposed by Moon, Ryu, Chun et al [16], or by Sodano and Rotinat-Libersa [24] for millimeter scale robot development. The purpose of the work reported in this paper is to investigate small-size hydraulic McKibben muscles working in a limited pressure range as developed by Tiwari, Meller et al [20], but with the additional constraint of functioning using small, low voltage pumps suitable for portable applications.…”
Section: Joseph L Mckibben Was the First To Introduce Mckibben Artifmentioning
confidence: 99%
“…Select research groups have utilized McKibben muscles hydraulically (Focchi et al, 2010;Meller et al, 2014b;Mori et al, 2010;Solano and Rotinat-Libersa, 2011;Tiwari et al, 2012). However, these actuators have not yet been fully characterized in the literature.…”
Section: Mckibben Artificial Musclesmentioning
confidence: 99%
“…Previous work with PAMs has focused on actuators with diameters on the order of an inch and lengths on the order of one foot. A PAM having such dimensions would be far too large for a MAV actuator, and thus a primary focus of the present work was to investigate PAM miniaturization using air as the working fluid as opposed to water as was done by Solano and Rotinat-Libersa (2011).…”
Section: Mini-pam Fabricationmentioning
confidence: 99%